Answers

Solutions by everydaycalculation.com

Everydaycalculation.com » Answers » Solve for x

Solve 3x + 3 = 6

How to solve 3x + 3 = 6? Get the answer and stepwise instruction to solve linear equation in one one variable 𝒙.

Steps for finding the solution

We have 3x + 3 = 6

First, we move the non x terms to the RHS of the equation. To do this, we subtract 3 from both sides.

Note: if a = b, then a - c = b - c

Therefore, 3x + 3 - 3 = 6 - 3

or, 3x = 3

Next, divide both sides by 3, which is the coefficent of x

Note: if a = b, then a ÷ c = b ÷ c

3x/3 = 3/3

x = 3/3

To simplify, divide both numerator and denominator by 3, which is the GCF of 3 and 3:

x = 1/1 or, x = 1

Solve another equation

𝒙 =

Related

© everydaycalculation.com